Morphometric Meristic and Growth Pattern Mystus nigricepsin the River, Pantai Cermin Village, Tapung Kiri River, Tapung district, Pekanbaru city, Riau province - Elfridayani, Tri; Putra, Ridwan Manda; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMystus nigriceps is a  fish that in habit the Tapung River. To understand the morphometrical and meristical characteristics and growth pattern of this fish, a research had been conducted from April to May 2018. There were 100 fishes (99.68-190.6 mm SL and 4.92-49.32 gr BW) were captured. There were 30 characteristics measured and 9 meristical characteristics counted. Results shown that there were 5 morphometrical characteristic differences between male and female. The head height, eye diameter, anal fin base, anal fin height and anal fin base length of the male are longer than those of the female. There were 2 meristical characteristic differences between male and female fish.  There was a white spot in the male’s fish tail and the shape of the male genital papila is pointed, while that of the female is blunt. The meristical characteristic of the fish were as follow: D.I.5-7; P.I-II.8-22; A.5-9; V.5-10.1; C.16-23.Mystus nigriceps do not have any scale,  but it has 4 pairs of barbels, 2 pairs in the  maxilla  and 2 pairs in the mandible.The length-weight relationship shown that the growth of male and female was similiar, it was negative allometric with  b=2.59in male and b=2.31in female. Keywords: Catfish, Morphological characteristics, Meristicalcharacteristic, growth pattern